Antecedents of logistics integration and firm performance for downstream petroleum supply chain. (22nd March 2019) - Sheel, Ashutosh; Singh, Y.P.; Nath, Vishnu
The present study tries to expand the current body of literature on supply chain integration, by studying the antecedents of logistics integration and firm performance in the context of the downstream petroleum supply chain in India. Data was collected from 348 petrol stations in the states of Uttarakhand, Uttar Pradesh and Haryana, India. Path analysis using structural equation modelling was performed to know the strength of the relationship between the identified variables. The findings show that long-term relationship affects firm performance. Also, information technology positively affects logistics integration, which positively affects firm performance. Based on these findings, the study proposes solutions to the issues being faced in the downstream petroleum supply chain in India. The current research applies past findings on supply chain integration in the context of downstream petroleum supply chains in India and addresses the lack of academic research as well as provides specific courses of actions as implications for the issues of downstream petroleum supply chains in India.